RELATIVE EXOCRINE INSUFFICIENCY OF PANCREAS IN CHILDREN - A. I. Khavkin (Вопросы современной педиатрии)
Diseases of gastro-intestinal tract are often accompanied by relative insufficiency of pancreas exocrine function, which can be asymptomatic, but demands including enzymes in complex treatment. The authors describe advantages of the microspheric enzyme drug Pancreatin (Creon) in treatment of different forms of relative exocrine insufficiency of pancreas in children.